The Relationship Between Negative Workplace Gossip and Job Satisfaction: A Study on the Mediating Role of Servant Leadership at IT&B Campus Medan - Hengky Kosasih (International Journal of Economics, Business and Innovation Research, 2025)
This study examines the impact of negative workplace gossip on job satisfaction among lecturers, focusing on the role of servant leadership as a mediating factor. The research was conducted at IT&B Campus Medan, with academic lecturers as respondents. Data was collected through both online and offline surveys. Data analysis was performed using Structural Equation Modelling (SEM) to evaluate the relationships among variables. The results indicate that negative workplace gossip negatively impacts job satisfaction, which can be minimized through servant leadership. Servant leadership was found to play a significant mediating role, improving interpersonal relationships and creating a supportive work environment, thereby enhancing job satisfaction. This study contributes to existing literature by providing empirical evidence of the mediating role of servant leadership in reducing the negative effects of gossip in academic settings, thereby enhancing our understanding of leadership dynamics in higher education institutions.